Integration of Internal-External Quality Assurance System as a Driver of Education Quality Improvement at MAN 14 Jakarta - Ahmad, Nurul Qomariyah; Riyadi , Riyadi; Soeprijanto , Soeprijanto; Badrujaman, Aip; Indrawati , Pipit (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
The importance of quality assurance in education in achieving the National Education Standards cannot be overstated. This study explores the potential of integrating the Internal Quality Assurance System (SPMI) and the External Quality Assurance System (SPME) as a strategy to enhance the quality of education in MAN 14 Jakarta. A qualitative research approach was adopted, with data collected through document review, observation, and in-depth interviews with relevant stakeholders. The findings indicate that the alignment between SPMI and SPME is evident in three primary domains: (1) the utilization of internal evaluation outcomes to bolster accreditation readiness, (2) the implementation of accreditation recommendations to catalyze continuous enhancement, and (3) the cultivation of a data-driven quality culture. This integrated approach has contributed to enhanced accreditation performance, fortified teacher capabilities, and cultivated an inclusive learning environment. Nevertheless, there are still some challenges to be addressed, such as the limited resources available for monitoring and a certain degree of resistance to change. In order to address these issues, this study proposes two solutions. Firstly, it suggests increasing human resource capacity. Secondly, it suggests integrating technology into the quality monitoring process. The findings of this study provide practical guidance for madrasahs that wish to strengthen their quality assurance systems in order to achieve excellence in education. Keyword SPMI, SPME, accreditation, quality assurance